Think Globally and Act Locally: Upaya Green School Bali Menjalankan Pembangunan Berkelanjutan (Sustainable Development) - Shertina, Rara (Global and Policy Journal of International Relations, 2020)
ABSTRACTSince its establishment in 2006, Green School Bali has aspired to create a sustainable world. Green School Bali has become a global movement by establishing Green Schools in New Zealand, Africa and Tulum. The Green School Bali has the largest bamboo building in Asia teaches its students the values of environmentalism. The founder of this school, John Hardy believes that climate change is a real issue that can destroy Earth. He feels that every human being should take an environmentally responsible approach and education is the starting point. Therefore, Green School builds a sustainable lifestyle by releasing its dependence on electricity and running various sustainable development programs. In this paper, the author will discuss how Green School Bali's efforts in carrying out sustainable development. The author will use the concept of sustainable development from several references to identify Green School Bali activities through several criteria. This is a qualitative research with descriptive research methods. The data taken in this paper is in the form of secondary data obtained from literature studies.Keywords: Sustainable Development, Green School Bali, Environmental ConservationSejak berdiri pada tahun 2006, Green School Bali telah bercita-cita untuk menciptakan sustainable world. Green School Bali telah menjadi sebuah global movement dengan mendirikan sekolah Green School di Selaindia Baru, Afrika dan Tulum. Sekolah dengan bangunan bambu terbesar di Asia ini mengajarkan siswanya nilai-nilai environmentalism. Pendiri sekolah ini, John Hardy percaya bahwa perubahan iklim adalah isu nyata yang dapat menghancurkan planet bumi. Ia merasa bahwa setiap manusia harus menggunakan pendekatan yang bertanggung jawab pada lingkungan dan pendidikan adalah titik awalnya. Maka dari itu, Green School membangun gaya hidup berkelanjutan dengan melepaskan ketergantunganya pada listrik dan menjalankan berbagai program pembangunan berkelanjutan. Dalam tulisan ini, penulis akan membahas bagaimana upaya Green School Bali dalam menjalankan sustainable development. Penulis akan menggunakan konsep pembangunan berkelanjutan dari beberapa rujukan untuk mengidentifikasi kegiatan-kegiatan Green School Bali melalui beberapa kriteria. Penelitian ini bersifat kualitatif dengan metode penelitian deskriptif. Data yang diambil dalam tulisan ini berbentuk data skunder yang didapat dari studi literatur.Kata-KataKunci: Sustainable Development, Green School Bali, Pelestarian Lingkungan Hidup